A bibliometric analysis of the scientific production of industry 4.0 and its relationship with the footwear industry (Research, Society and Development, 2021)
This article sought to show the growth of scientific production and to map the main studies referring to industry 4.0 in the last five years, highlighting its main characteristics and technologies. The work showed the relationship of the theme with one of the most traditional industries responsible for regional development in several countries, the footwear industry. The work also revealed the relationship with industry 4.0, showing that there are still gaps, and possibilities for promising studies involving themes mainly in the area of desing for the footwear industry. The research was carried out on the Web of Science database, which pointed out the main articles published in the period. A systematic review of the literature was carried out to show the ancestry of the studied themes. It is possible to affirm that the theme of industry 4.0 has increasingly shown its relevance with the growth of research. The engagement of the footwear industry with the implementation of industry 4.0 tools may allow advances in the formulation of competitive strategies for the sector.